A Positive Zonal Wind Feedback on Sudden Stratospheric Warming Development Revealed by CESM2 (WACCM6) Reforecasts. Issue 5 (8th March 2021) - Davis, Nicholas A.; Richter, Jadwiga H.; Edwards, Jim; Glanville, Anne A.
Abstract: Sudden stratospheric warmings (SSWs) are an extreme weather event with impacts on the ionosphere and on tropospheric weather and predictability. The mechanisms governing their formation remain elusive, despite their deterministic predictability at nearly 2 weeks. This study uses high resolution CESM2 (WACCM6) subseasonal reforecasts to examine the dynamics that differentiate successful and unsuccessful SSW predictions. Successful reforecasts are generally initialized with a weaker stratospheric jet. However, the basic relationships between jet deceleration, wave drag, and the residual mean angular momentum flux do not fundamentally differ between successful and unsuccessful reforecasts. Instead, the projection of the residual circulation onto a weakened jet produces a weaker angular momentum flux, which leads to a more rapid erosion of the jet as the residual circulation cannot effectively balance the sustained wave drag. This information could be used to develop forecasting practices that could probe the likelihood of SSWs at longer timescales. Plain Language Summary: Sudden stratospheric warmings (SSWs) are rapid breakdowns of the stratospheric polar vortex. The sudden change in winds eventually reaches the surface and creates predictable weather patterns, leading to improved weather forecasts. SSWs are driven by turbulently breaking atmospheric waves, sort of like waves breaking on a beach. By looking at forecasts of different SSWs over the past 20 years, this study shows that there is an important feedback that helps these breaking waves destroy the vortex. When the vortex weakens slightly due to breaking waves, the vortex becomes less efficient at rebuilding itself. If this happens frequently enough, it amplifies the effect of the waves and helps them destroy the vortex. It may be possible to encourage this feedback in weather forecasts to better determine the likelihood of a sudden warming occurring. Key Points: In WACCM6, sudden stratospheric warming (SSW) prediction is improved when reforecasts are initialized with a weak stratospheric jet A weaker jet reduces the angular momentum transport by the residual circulation, maintaining the dynamical cascade to a sudden warming Simple forecasting practices could better initiate this feedback in WACCM6 and potentially improve SSW prediction